Contributions of Information Design in the data visualization of a popular lettering’s research - Ardisson Bento, Amanda; Antônio Silva, Sérgio; Pedruzzi Fonseca, Letícia (InfoDesign, 2023)
In Brazilian graphic design, there is a growing movement that seeks to value manifestations of urban and popular graphics in search for its identity. An example is the popular lettering produced by professional letter painters and found in several cities across the country. To value them, it was developed a research that investigated its production in the Vitória’s Wide Metropolitan Area (ES) to search and recognize local styles that can attest their graphic identity. In the history design studies’ field, methodological procedures were adapted that enabled to its collection, cataloging, and analyzing its letters’ formal aspects and style, as well as the investigation of techniques and working methods of its creators. The aim of this paper is to present the adaptation in the methodological way and how Information Design procedure were used to visualize the research data. With the research results, the main aspects of popular lettering in relation to technological, social and cultural issues were identified, providing discussions the promote the Brazilian Graphic Memory and capixaba’s.